Jenis Kelamin Ikan Nilem (Osteochilus hasseltii) Berdasarkan Truss Morfometrik di Sungai Banjaran, Kabupaten Banyumas - Widayanto, Imanuel Eka; Muslih, Muslih; Sari, Lilik Kartika (MAIYAH, 2023)
Osteochilus hasseltii belongs to the Cyprinidae family and is a native species in the Banjaran River. Populations of O. hasseltii that are continuously exploited can cause the population to decrease and cause an imbalance between males and females. This study aims to determine differences in morphology and sex of O. hasseltii. The research method uses a survey method and purposive random sampling at two stations, namely Kober Village and Kedung Wuluh Village. A total of 16 individuals of O. hasseltii (8 males and 8 females) were caught using fishing rods. About 24 morphometric truss distances were measured using Image-J software. Normality and homogeneity tests need to be done before conducting the t-test. Data analysis used the t-test with the help of Minitab software. The morphological characters of O. hasseltii seen from the dendogram can be seen that each truss distance measured on male O. hasseltii has a similarity of above 90% so that the morphological differences and the similarities are small. Whereas in female O.hasseltii, the similarity exceeds 75% at each truss distance so that the distinguishing character of female O.hasseltii can be seen from the truss distance which has a small similarity, namely Anal-fin base length (Q) of 76.14% and Upper-jaw length (D) of 86.3%. The results of the t-test showed 8 morphometric truss distances that could be used as a distinguishing feature of male and female O. hasseltii is Snout-supraoccipital distance, Snout length, Snout-pectoral distance, Snout-gill distance, Postorbital head length, Gill-pelvic distance, Dorsal-pelvic distance, and Dorsal fin base length. Therefore, the morphometric truss can be used to differentiate the sex of O. hasseltii.